2015
DOI: 10.1007/s12528-015-9094-5
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated versus non-facilitated online case discussions: comparing differences in problem space coverage

Abstract: The facilitator plays a key role in guiding students' efforts during case discussions. However, few studies have compared differences in learning outcomes for students participating in facilitated versus non-facilitated discussions. In this research, we used ''problem space coverage'' as a learning measure to compare outcomes between facilitated (F) and non-facilitated (NF) online case-based discussions. In general, results demonstrated both greater and deeper problem space coverage during facilitated discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…When exploring tutorless PBL in online environments, Fonteijn (2015) found that learners were able to thrive when afforded more autonomy and ICT support such as mapping software and communication tools. Ertmer and Koehler (2015), on the other hand, found that facilitated online discussions were superior to non-facilitated discussions. Woods, Duncan-Hewitt, Hall, Eyles, and Hrymark (1996) found that tutorless PBL groups experienced difficulty in workload distribution, building trust, and reliability.…”
mentioning
confidence: 97%
“…When exploring tutorless PBL in online environments, Fonteijn (2015) found that learners were able to thrive when afforded more autonomy and ICT support such as mapping software and communication tools. Ertmer and Koehler (2015), on the other hand, found that facilitated online discussions were superior to non-facilitated discussions. Woods, Duncan-Hewitt, Hall, Eyles, and Hrymark (1996) found that tutorless PBL groups experienced difficulty in workload distribution, building trust, and reliability.…”
mentioning
confidence: 97%
“…Ertmer and Koehler (2015) found the frequency of students' postings was not related to the frequency of instructor postings. However, they interpreted the quality of the discussion more highly with an instructor's presence.…”
Section: Teaching Presence and Online Discussionmentioning
confidence: 82%
“…Furthermore, prospective teachers may start with predispositions toward simplifying the situation and identifying issues from a single perspective when they engage in a case reading. Prospective teachers' reflective and critical thinking skills can be facilitated through discussions of the case (Butler et al, 2006;Ertmer & Koehler, 2015). Online or face-to-face discussions play a very important role to be able to provide opportunities to analyze case dilemmas from various perspectives and to restructure prospective teachers' beliefs about teaching and learning.…”
Section: Case-based Pedagogymentioning
confidence: 99%
“…There are several studies reporting the effects and comparisons of online and face-to-face case discussions in the literature (Ertmer & Koehler, 2015;Mitchem et al, 2008;Weil, McGuigan, & Kern, 2011). Ertmer and Koehler (2018) stated that the structure and facilitation of the discussion, as well as guiding questions and responses by the facilitator should be specifically designed to provide effective case-based discussion experiences.…”
Section: Case-based Pedagogymentioning
confidence: 99%